PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP TERJADINYA PERNIKAHAN USIA MUDA DI DESA SEUMADAM KECAMATAN KEJURUAN MUDA KABUPATEN ACEH TAMIANG TAHUN 2014 - siti zubaidah harahap; Heru Santosa; Erna Mutiara (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACTEarly marriage is a holly/sacred relationship between a man and a woman who had age under 19 years or were currently enrolled in high school and the relationship have been legally recognized in law and religion.The purpose of research was to know the influence of internal and external factors on early marriage among teens at Seumadam Village, Kejuruan Muda Subdistrict, Aceh Tamiang District. This was observational research with a cros-sectional approach. Population were all teens of 15-19 years as many as 556 people. Samples of the research were married teens aged 15-19 years, or who have a boyfriend or were engaged as many as 95 people. Data were obtained through interview using a questionnaire and analyze with the step of univariate, bivariate using chi square test and multivariate using multiple logistic regression test.The result showed that respondents marriaged at age 15-19 year were 26,3%. There was an influence of knowledge, emotional maturity, culture, exposure to mass media and free sex on early marriage among teens. The variable that most influenced on early marriage among teens was culture with the coefficient of B = 3.404.It is suggested to the Seumadam Village to cooperate with the local government such as institution of religion affair office, education and health to reactivate PIK-KRR (information center of counseling adolescence reproductive health) as a forum to get information about complication a pregnancy problem.Keyword : Early Marriage, Teens